Endowments vs market potential: what explains the relocation of industry after the Polish reunification 1918? - Nikolaus Wolf (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
How did the location of industry across interwar Poland react to the Polish reunification? After more than 120 years of political and economic separation, Poland was reunified at the end of 1918. In consequence, the removal of internal tariff barriers and improved infrastructure strengthened the domestic market, while foreign market relations were cut off. Similarly, the geographical distribution of factor endowments was changed, for example through internal migration. How did these forces interact to determine the location of industry? We survey the dynamics of industrial location between 1902 and 1925-1937 and estimate a specification that nests market potential and comparative advantage to quantify their respective impact during the interwar years. The results point to a role for both, comparative advantage and access to markets. We show that both statistically and economically the most important factors were the endowment with skilled labour and interindustry-linkages.
Keywords: F10; F11; F12; F14; F15; N74; R3; 330; Industriestandort; Regionale Arbeitsteilung; Faktorproportionentheorem; Wirtschaftsgeschichte; Polen